Where Patients With Cancer Die: A Population-Based Study, 1990 to 2012. Issue 4 (October 2019) - Hunt, Roger W.; D'Onise, Katina; Nguyen, Anh-Minh Thi; Venugopal, Kamalesh
Aims: To describe changes in the place of death of patients with cancer from 1990 to 2012, and to identify issues for their end-of-life care. Materials and Methods: Population-based descriptive study, with analyses of place of death patterns, using the South Australian Cancer Registry records of 86 257 patients with cancer who died from 1990 to 2012. Results: From 1990 to 2012, the proportion of cancer deaths in hospital decreased from 63.4% to 50.9%, and in nursing homes increased from 8.2% to 22.5%. After the year 2000, the proportions in hospices and at home were both below 15%. Multivariate analyses showed that young patients with cancer were more likely to die in a hospice or at home, compared to elderly patients with cancer who were more likely to die in a nursing home; the likelihood of dying in a hospice increased with socioeconomic status; patients with a short survival time or a hematological malignancy were more likely to die in a metropolitan hospital. Conclusions: Compared to most other countries, the proportion of cancer deaths at home was low, and many patients would not have died at their preferred place. The trend for more cancer deaths to occur in nursing homes is likely to continue, but nursing homes generally lack the resources and skilled staff to provide quality palliative care. Models of palliative care delivery should take account of patient preferences, the growth of terminal cancer care in nursing homes, and apparent inequities.